Bioinputs in the germination and initial development of Vachellia caven (Molina) Seigler & Ebinger - Corrêa, Gabriela Neves Righi; Quatrin, Marciéli; da Silva, Antonio Carlos Ferreira; Ebone, André; Stefanello, Raquel; Vestena, Silvane (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Vachellia caven (Molina) Seigler & Ebinger, a species found in Rio Grande do Sul, is considered a precursor species, and when it comes to reforestation, organisms like this are of the utmost importance. The use of compounds with bacteria can help with the germination and initial growth of plants and control phytopathogens, while also reducing the need for fungicides and fertilizers, which are often harmful to the soil and the environment. Organisms such as Bacillus subtilis, B. megaterium, B. amyloliquefaciens, Azospirillum brasilense, Pseudomonas fluorescens and Priestia megaterium can be used for this purpose. The aim of this study was to evaluate the results of different bioinputs on the germination and initial growth of V. caven. To this end, seed dormancy was overcome with concentrated sulfuric acid for two hours, and seven treatments were used, two of which were control treatments (one with water and the other with mineral oil) and five treatments with bioinputs. Each treatment had four replicates with 50 seeds each. The seeds were sown on germitest paper and kept in a growth chamber. Parameters such as first germination count, germination, shoot and root length, and shoot and root dry mass were assessed. After analysis, it was possible to see that under the conditions tested, there was no increase or decrease in the germination rate of V. caven. This infers that the bioinputs used, as they have a neutral action on the germination and initial growth of V. caven, may be safe if they are used in biological control of phytopathogens, nitrogen fixation, and other nutrients, with a view to producing seedlings of this plant species.